Efficiency of Sodium and Calcium Chloride in Conferring Cross-Tolerance to Water Deficit in Periwinkle - Zomorrodi, Nahid; Rezaei Nejad, Abdolhossein; Mousavi-Fard, Sadegh; Feizi, Hassan; Nikoloudakis, Nikolaos; Fanourakis, Dimitrios (My University, 2022)
The potential of using pre-stress NaCl or CaCl2 applications to confer a cross-tolerance to a water deficit was evaluated in periwinkle. The plants initially received five applications of NaCl (0, 30 and 50 mM), or CaCl2 (15 and 25 mM) via irrigation, and then they were cultivated under different water deficit regimes (80, 50 and 20% available water content). The water deficit induced smaller and denser stomata. It promoted a water use efficiency, a proline content and antioxidant enzyme activity. However, it downgraded the aesthetic value (plant stature, flower size and vegetation greenness), magnified the stem bending probability and strongly decreased the floral longevity. It additionally impeded the growth by reductions in the leaf area and photosynthesis. Plants undergoing a water deficit maintained a lower hydration and expressed oxidative damage symptoms, including enhanced chlorophyll and membrane degradation. As the water deficit intensified, these effects were more pronounced. Pre-stress CaCl2 or NaCl applications generally restored most of the water severity-induced effects, with the former being more effective. For CaCl2, the highest concentration (25 mM) was generally optimal, whereas NaCl was the lowest concentration (30 mM). In conclusion, pre-stress CaCl2 or NaCl applications effectively confer a cross-tolerance to the water deficit by promoting the aesthetic value and extending the floral longevity, with the promotive effects being incremental as the water deficit becomes more severe.
Keywords: antioxidant defense; biomass accumulation; carbon assimilation; Catharanthus roseus; cellular damage; stomatal traits; water deprivation